Microbiology and immunology: An ideal partnership for a tango at the gut surface—A tribute to Philippe Sansonetti. (26th August 2019) - Cerf‐Bensussan, Nadine
Abstract: Over the past 20 years, the highly dynamic interactions that take place between hosts and the gut microbiota have emerged as a major determinant in health and disease. The complexity of the gut microbiota represents, however, a considerable challenge, and reductionist approaches are indispensable to define the contribution of individual bacteria to host responses and to dissect molecular mechanisms. In this tribute to Philippe Sansonetti, I would like to show how rewarding collaborations with microbiologists have guided our team of immunologists in the study of host–microbiota interactions and, thanks to the use of controlled colonisation experiments in gnotobiotic mice, toward the demonstration that segmented filamentous bacteria (SFB) are indispensable to drive the post‐natal maturation of the gut immune barrier in mice. The work led with Philippe Sansonetti to set up in vitro culture conditions has been one important milestone that laid the ground for in‐depth characterization of the molecular attributes of this unusual symbiont. Recent suggestions that SFB may be present in the human microbiota encourage further cross‐fertilising interactions between microbiologists and immunologists to define whether results from mice can be translated to humans and, if so, how SFB may be used to promote human intestinal defences against enteropathogens. Nurturing the competences to pursue this inspiring project is one legacy of Philippe Sansonetti.